THE LEVEL OF KNOWLEDGE ABOUT RISK FACTOR FOR HYPOGLYCEMIA AMONG DIABETES MELLITUS PATIENT IN PRIMARY HEALTH CENTER TEGALLALANG I REGION, BALI PROVINCE - Darmayani, Gusti Ayu Putu Melisa Sinta Melenia; Sari, Ni Komang Ayu Kartika; Sawitri, Anak Agung Sagung (E-Jurnal Medika Udayana, 2023)
The level of knowledge about risk factors for hypoglycemia or blood sugar levels below normal has not been researched widely in patients with diabetes mellitus. This study aims to determine the level of knowledge about risk factors for hypoglycemia in patients with diabetes mellitus. A cross-sectional descriptive study was conducted on patients with diabetes mellitus with aged more than 20 years at the Tegalallang I Public Health Center in the last 1 year. The research sample was taken by accidental sampling on 90 respondents. The knowledge level of diabetes mellitus patients about risk factors for hypoglycemia was measured by 10 questions, while the characteristics measured were age, gender, last education level, socio-economic conditions, duration of diabetes mellitus, sources of information, and experience suffering from hypoglycemia. Data were analyzed using statistical applications through descriptive analysis and cross tabulation. The results of this study found that most respondents have good knowledge (55.6%). Good knowledge is distribute on age 20-29 and 30-39 years old (100%), female (65.2%), having the last education of SMA/SMU (87%) and Bachelor (75%), and earning below Rp. 2,600,000 (56.2%). In addition, the majority of patients with good knowledge had the characteristics of having diabetes mellitus under 5 years (58.3%), received information from children (100%), and had experienced hypoglycemia before (61.5%). The knowledge level of patients with diabetes mellitus about risk factors for hypoglycemia in patients with diabetes mellitus is mostly good.